Design, synthesis, molecular docking, and biological studies of novel phytoestrogen-tanaproget hybrids. Issue 5 (3rd March 2016) - Kumar, Sumit; Verma, Nishant; Kumar, Nikhil; Patel, Alok; Roy, Partha; Pruthi, Vikas; Ahmed, Naseem
ABSTRACT: A diverse range of novel and highly functionalized flavonoid-based tanaproget hybrids were synthesized and evaluated in vitro for their antimicrobial and antiproliferative activities. Novel products were synthesized in good yields (81–95%) under Pd-catalyzed reaction from bromo flavones and tanaproget boronic acids within 18–20 min at 60 °C. Bioassay results exhibited excellent activities against both hormone-dependent and hormone-independent human breast cancer cells (MCF-7, MDA-MB-231, DU-145, PC-3, and HeLa). Among them, compounds4e, 9a, 9c, 9e, 9 g, 9 h, 9 m, and9n displayed excellent activity. Compounds4d, 4o, and9o were found equally potent against C. albicans compared to fluconazole. Compound5c showed better antibacterial activity against S. aureus . Compounds5a, 9i, 9o, and10c have shown admirable antibacterial activity against E. coli . GRAPHICAL ABSTRACT: